Initiating The Extra Judicial Review Model as a Form of Balancing the Power of The Veto in Overcoming International Armed Conflicts - Pravidjayanto, Rafi; Rohmatullah; Fran’s Hidayatullah (Al-Jinayah : Jurnal Hukum Pidana Islam, 2024)
In the United Nation structure there are important organs, one of which is the Security Council which plays an active role in resolving international disputes carried out by the parties. However, the settlement of such disputes is often hampered by vetoes proposed by the five permanent members of the UNSC including China, Russia, the United States, France, and the United Kingdom, so the use of veto power in this case has shifted to protect the interests of the country. By using juridical-normative methods through conceptual and historical approaches and using qualitatively analyzed literature data. The results showed that there is still no clear regulation regarding the consideration of permanent members in issuing veto rights. The recommendation given is in the form of an appeal mechanism (extra judicial review) for denial of the principle of Soveregein Equality because the existence of veto power is still problematic in realizing balancing between countries. The hope is that there is a decision-making mechanism in the UN Security Council that is more equitable by applying positive consensus in realizing peacekeeping missions.